Pengembangan LKPD Berbasis Role Playing Pada Pembelajaran IPAS Dalam Kurikulum Merdeka Dengan Materi Indonesiaku Kaya Budaya Untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Nurul Sahpitri Tanjung; Sri Ramadhina; Syahrial Syahrial (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve thematic LKPD learning using a role-playing model in grade 5 elementary schools in Bengkulu City.This research is research and development (R&D) carried out by modifying Thiagarajan and Sammel's four-dimensional model.This research shows that LKPD in thematic learning using the role-playing model received a score of 78.10 in the